2020
DOI: 10.3390/ijms21197240
|View full text |Cite
|
Sign up to set email alerts
|

Biological Functions of Prokaryotic Amyloids in Interspecies Interactions: Facts and Assumptions

Abstract: Amyloids are fibrillar protein aggregates with an ordered spatial structure called “cross-β”. While some amyloids are associated with development of approximately 50 incurable diseases of humans and animals, the others perform various crucial physiological functions. The greatest diversity of amyloids functions is identified within prokaryotic species where they, being the components of the biofilm matrix, function as adhesins, regulate the activity of toxins and virulence factors, and compose extracellular pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 189 publications
0
19
0
Order By: Relevance
“…It has become increasingly clear that amyloid structures are not only found in aberrant and disease-related aggregates, but also in functional protein assemblies referred to as “functional amyloids” [ 7 ]. Functional amyloids are mainly produced by prokaryotes [ 6 , 55 ] and some of them are produced by higher eukaryotes [ 56 ]. It is currently understood that functional amyloids serve diverse purposes, and some of them act as biofilm matrix proteins playing a scaffolding role in microorganisms [ 6 , 55 ].…”
Section: Kinetic and Thermodynamic Controls In Functional Amyloid Structuresmentioning
confidence: 99%
See 3 more Smart Citations
“…It has become increasingly clear that amyloid structures are not only found in aberrant and disease-related aggregates, but also in functional protein assemblies referred to as “functional amyloids” [ 7 ]. Functional amyloids are mainly produced by prokaryotes [ 6 , 55 ] and some of them are produced by higher eukaryotes [ 56 ]. It is currently understood that functional amyloids serve diverse purposes, and some of them act as biofilm matrix proteins playing a scaffolding role in microorganisms [ 6 , 55 ].…”
Section: Kinetic and Thermodynamic Controls In Functional Amyloid Structuresmentioning
confidence: 99%
“…Functional amyloids are mainly produced by prokaryotes [ 6 , 55 ] and some of them are produced by higher eukaryotes [ 56 ]. It is currently understood that functional amyloids serve diverse purposes, and some of them act as biofilm matrix proteins playing a scaffolding role in microorganisms [ 6 , 55 ]. In filamentous fungi, amyloid fibrils organize an amphipathic monolayer by assembling laterally on the surface of a hydrophobic/hydrophilic interface, thus reversing wettability, as seen in water-repellent spore coats [ 57 ].…”
Section: Kinetic and Thermodynamic Controls In Functional Amyloid Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Amyloids have also an RNA-modulating ability and play a role in transcription, translation, storage and degradation of RNA [ 173 ]. It has been shown that some motifs in prions of fungi and humans can be functionally related and be a model of amyloid signaling mechanisms from fungi to mammals [ 174 , 175 ]. Prokaryotic cells can also use such properties [ 8 ].…”
Section: Useful Properties Of Amyloids Functional Amyloidsmentioning
confidence: 99%